A History of and Recent Developments Concerning the Korean Peninsula Northern Limit Line (NLL). (2nd October 2019) - Kyoon Kim, Suk
Abstract: Measures to ease tensions and prevent military conflicts adjacent to the Korean Peninsula Northern Limit Line (NLL) are an integral part of the ongoing reconciliatory efforts between the South and the North. Despite controversies over the validity of the NLL, it has served as a de facto maritime demarcation line in the absence of an agreed-upon maritime demarcation line under the Armistice Agreement. North Korea has persistently attempted to invalidate the NLL, while South Korea has supported the status quo of the NLL as a military demarcation line. The South and North have recently created a buffer zone across the NLL in the West Sea amid talks for North Korea's denuclearization.